2006
DOI: 10.1007/s10803-006-0279-7
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the Social Communication Questionnaire in Assessing Risk of Autism in Preschool Children with Developmental Problems

Abstract: This study estimates the sensitivity and specificity of the social communication questionnaire (SCQ) for autistic spectrum disorders in preschool children at high risk for developmental problems referred to a tertiary centre and compares the predictions of the SCQ and the referrer. The SCQ was completed by 81 parents prior to multidisciplinary assessment and compared with the final diagnosis. The sensitivity and specificity were 93% and 58% for children aged 2-6, and 100 and 62% for children aged 3-5 years, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
128
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(140 citation statements)
references
References 16 publications
9
128
0
1
Order By: Relevance
“…Consistent with previous research, our young sample scored lower on the SCQ than children roughly over 8 years tend to do (Allen et al 2006;Berument et al 1999;Corsello et al 2007). Considering this optimal cutoff for young children, Corsello et al studied the SCQ used as a secondary screening tool in a young age group (\5 years, N = 201).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Consistent with previous research, our young sample scored lower on the SCQ than children roughly over 8 years tend to do (Allen et al 2006;Berument et al 1999;Corsello et al 2007). Considering this optimal cutoff for young children, Corsello et al studied the SCQ used as a secondary screening tool in a young age group (\5 years, N = 201).…”
Section: Discussionsupporting
confidence: 85%
“…Using a cut-off of 11 would increase the sensitivity to 0.80, with specificity decreasing to 0.60. Allen et al (2006) also used the SCQ as a secondary screening instrument with a cut-off of 15 and 11, and found a sensitivity of 0.56 and 0.89 and a specificity of 0.29 and 0.29 respectively in a group of children aged 24-36 months (N = 16). In addition, Wiggins et al (2007) found a high sensitivity (0.89) together with a surprisingly high specificity (0.89) while using a cut-off of 11 in a clinical sample referred for early intervention (N = 37, age-range 17-45 months).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The measure has well-established reliability and validity (Rutter et al 2003). Scores above 15 suggest that the individual is likely to have ASD; a cutoff of 11 has been used successfully in determinations of sensitivity (Allen et al 2007). The Autism Diagnostic Observation Schedule 2 (ADOS-2; Lord et al 2012), a semi-structured observational procedure for assessing autism spectrum disorder, was used to confirm clinical diagnoses of ASD that parents reported.…”
Section: S C R E E N I N G a N D D I A G N O S I S O F A S D T H E S mentioning
confidence: 99%
“…Lowering the cut-off score to 11 or more items in this age group has been suggested (Allen, Silove, Williams, & Hutchins, 2007;Corsello, et al, 2007). In this study, the Dutch translation of the SCQ 'current' was used (Warreyn, Raymaekers, & Roeyers, 2004) and the cut-off score was set on 11 or more items.…”
Section: Social Communication Questionnaire (Scq;mentioning
confidence: 99%